PENYUSUNAN JURNAL UMUM MENGGUNAKAN APLIKASI MICROSOFT EXCEL PADA USAHA MIE CRUWELL WLINGI - Enola Helmania Normansyah; Latifah, Nunuk; Wardani, Shanti Ike (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2022)
Objective. The preparation of a general journal in the Mie Cruwell Wlingi business which is still simple by using manual recording on books, all expenditure transactions are still recorded on paper that is at risk of being lost. The purpose of this study was to determine the stages in compiling a general journal and to find out the obstacles in compiling a general journal in the Mie Cruwell Wlingi business. Materials and Methods. This research is descriptive qualitative and by using interview and documentation techniques. Interviews were conducted with 2 (two) informants, namely business owners and employees. Documentation is in the form of photos of documents needed by research as well as results of interviews. Data analysis techniques obtained through data reduction, data presentation and Conclusion Drawing according to the problem. Results. The results of the study can be concluded that the preparation of general journals in the Cruwell Wlingi Noodle business is still done manually. The owner will implement the preparation of the general journal by utilizing the Microsoft Excel application, and the owner is still experiencing problems in the preparation of the general journal. Conclusion. The preparation of the general journal on the Cruwell Wlingi Mie business is still done manually. The owner will implement the preparation of the general journal by utilizing the Microsoft Excel application, so that business owners in compiling the general journal are easier, neater and less time consuming. Owners have problems in preparing general journals, such as owners do not understand how to enter transactions into journals, do not know how to make general journals using Microsoft Excel application, need time to learn how to compile general journals using Microsoft Excel applications.